Radiocarbon dates of mammoth finds in Finland compared with radiocarbon dates of Weichselian and Eemian deposits - J. Donner; H. Jungner; B. Kurtén (Bulletin of the Geological Society of Finland, 1979)
In Finnish Lapland the Weichselian Peräpohjola Interstadial can be separated from the Eemian Interglacial with the help of the tree pollen composition of organic deposits between tills. In southern Finland the redeposited organic matter is either interstadial or interglacial. All organic deposits are too old to be dated with conventional radiocarbon methods. The three radiocarbon ages of mammoth finds, 15500 ± 200, 25200 ± 500 and > 43000, and an earlier date of 34300 +2000/-1450 of a reindeer antler, suggest that large parts of Finland were ice-free in Middle Weichselian time, a time from which no remains of organic deposits have been found. The youngest date does not agree with the deglaciation chronology.